Substrate placement angle-dependent growth of Ga/F co-doped ZnO nanostructures synthesized by hydrothermal process - Chongsri, Krisana; Boonyarattanakalin, Kanokthip; Pecharapa, Wisanu (My University, 2017)
In this work, the effect of angle-dependent substrate placement on structural property and morphology of Ga/F co-doped ZnO nanostructures was investigated. The Ga/F co-doped ZnO (GFZO) nanostructures were grown on substrates with ZnO seeding layer placed at different tilted-angle by a hydrothermal process using Zn(NO3)2, NH4F, GaN3O9 for Zn, F and Ga sources and hexamethylenetetramine as sol stabilizer. The ZnO seeding layer was pre-deposited on glass substrates by dip-coating. The GFZO nanostructures were grown on ZnO substrate at different tilted-angles from 0° to 180° with respect to horizon. The effects of tilted angle of placed substrate on morphologies and structural properties were investigated by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), and UV–Vis spectroscopy. The results indicate that this growth parameter has a vital role on preferable growth direction, morphological structure and shape of the as-synthesized nanostructure products.
Keywords: A. Grain growth; A. Sol–gel processes; B. Impurities; D. ZnO